Analisis Multiplier Effect Pengembangan Sistem Mina Padi Bagi Masyarakat Lokal di Desa Epeesi Kecamatan Basala Kabupaten Konawe Selatan - Ningrum, Noven Zelisqian; Limi, Muhammad Aswar; Fyka, Samsul Alam (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to determine the characteristics of economic activities arising from the existence of the rice mina system and the multiplier effect of the development of the rice mina system for local communities in Epeesi Village, Basala District, Konawe Selatan District. This research was conducted in 2019. The analysis used was qualitative analysis and quantitative analysis. The results of this study indicate that the economic activities that arise as a result of the development of the rice mina system are the existence of a business unit developed in the form of fishing tours and fish sales with an income of an average of Rp. 18,211,764 / year and an average of Rp. 14,000,000 for the sale of fish. The multiplier effect value obtained from the Keynesian Income Multiplier value is 2.5, the Type I Ratio Income Multiplier is 1.0 and the Type II Ratio Income Multiplier is 1.1. The existence of rice mina system development activities provides a good economic impact for the community, especially activists of the rice mina system, this is because the multiplier value is a large effect of one (> 1).